2006
DOI: 10.1007/s11104-006-9137-9
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-mediated changes of some physiological and enzymatic parameters symptomatic for oxidative stress in spinach and tomato grown in sodic-B toxic soil

Abstract: We investigated effect of silicon (Si) on the growth, uptake of sodium (Na), chloride (Cl), boron (B), stomatal resistance (SR), lipid peroxidation (MDA), membrane permeability (MP), lipoxygenase (LOX) activity, proline (PRO) accumulation, H 2 O 2 accumulation, nonenzymatic antioxidant activity (AA) and the activities of major antioxidant enzymes (superoxide dismutase, SOD; catalase, CAT and ascorbate peroxidase, APX) of spinach and tomato grown in sodic-B toxic soil. Si applied to the sodic-B toxic soil at 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(127 citation statements)
references
References 50 publications
9
99
1
8
Order By: Relevance
“…This study showed that lipid peroxidation induced by NaCl was lower in the Si-treated rice seedlings under salt stress than those under salt stress without Si treatment, which revealed protection of lipid membranes from ROS [47], primarily by more effective scavenging of ROS by means of Si application. Similarly, Si application decreased malondialdehyde and H 2 O 2 contents in spinach and tomato plants grown in sodic-B toxic soil [48].…”
Section: Discussionmentioning
confidence: 87%
“…This study showed that lipid peroxidation induced by NaCl was lower in the Si-treated rice seedlings under salt stress than those under salt stress without Si treatment, which revealed protection of lipid membranes from ROS [47], primarily by more effective scavenging of ROS by means of Si application. Similarly, Si application decreased malondialdehyde and H 2 O 2 contents in spinach and tomato plants grown in sodic-B toxic soil [48].…”
Section: Discussionmentioning
confidence: 87%
“…The application of phosphate simultaneously with arsenate ameliorate to some extent the damaging effect caused by arsenic toxicity. Therefore, the use of phosphate enriched fertilizers in arsenic contaminated soils may improve the health with better sugar metabolizing activity as well as production of rice plants, but the concentration of phosphorus in fertilizers should be carefully considered (Gunes et al, 2008).…”
Section: Effect Of Arsenate and Phosphate On Carbohydrate Metabolismmentioning
confidence: 99%
“…However, the role of silicon in crops is not particularly well understood (Casey et al 2003). Silicon plays a very important role in the reduction of the plants vulnerability to biotic and abiotic environmental stress (Fauteux et al 2005, Mitani and Ma 2005, Ma and Yamaji 2006, Liang et al 2006, Gunes et al 2007, Sacała 2009). This component increases the plants' resistance to pathogens and pests (Samuels et al 1993, Fawe et al 1998, Raven 2003, Henriet et al 2006, Cai et al 2009).…”
mentioning
confidence: 99%